PENGEMBANGAN UTILITY PENCETAKAN DAFTAR HADIR KULIAH JURUSAN ILMU KOMPUTER FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNIVERSITAS LAMPUNG - Dwi Sakethi; Anie Rose Irawati; Aqillah Aliffah Kadir (Universitas Lampung, 2015)
In 2013, the research developed a Printing Utility Lecture’s Attendance using web base of Sistem Matahari. But, due to changes in database and language of SIAKAD (Academic System Information) University of Lampung in 2014, then the utility cannot be reused. To solving the problem, this research had successfully developed a Printing Utility of Lecture’s Attendance List, case study of Development of Computer Science, FMIPA University of Lampung. The making of attendance list is using data source from result from imported excel file format DNK (List of Student Name in A Class) retrieved from SIAKAD University of Lampung. The development is also done on improving attendance list printout with the output of a dynamic PDF file that is can be customized to user requirements.Keyword: Utility, Excel to Database, Lecture’s Attendance List